2013
DOI: 10.1142/s1084946713500131
|View full text |Cite
|
Sign up to set email alerts
|

Sudanese Women Entrepreneurs

Abstract: The number of female entrepreneurs is growing around the globe. The rate of women's entrepreneurship in Africa is higher than in any other region of the world but no studies have focused on North Sudan. We investigate female entrepreneurs in North Sudan by addressing these questions: (1) What are the major challenges North Sudanese female entrepreneurs face in (a) venture startup, and (b) running their businesses, (2) What are the main support sources enabling North Sudanese female entrepreneurs' (a) venture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…The level of work-family balance is often assumed to be closely related to the level of family moral support and cooperation (Kim & Ling, 2001;Rehman & Roomi, 2012;Shelton, 2006), an important factor involved in women's entrepreneurial processes (Chang et al, 2009;Chang, Memili, Chrisman, & Welsh, 2012;Welsh, Kim, Memili, & Kaciak, 2014a;Welsh, Memili, Kaciak, & Ahmed, 2013;Welsh, Memili, Kaciak, & Ochi, 2014b). The moral support measure used in this study involves the family moral supporters (spouse, child, parent, sibling and/or relative) as well as several non-family moral supporters (friend, mentor, government agency and/or private agency).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The level of work-family balance is often assumed to be closely related to the level of family moral support and cooperation (Kim & Ling, 2001;Rehman & Roomi, 2012;Shelton, 2006), an important factor involved in women's entrepreneurial processes (Chang et al, 2009;Chang, Memili, Chrisman, & Welsh, 2012;Welsh, Kim, Memili, & Kaciak, 2014a;Welsh, Memili, Kaciak, & Ahmed, 2013;Welsh, Memili, Kaciak, & Ochi, 2014b). The moral support measure used in this study involves the family moral supporters (spouse, child, parent, sibling and/or relative) as well as several non-family moral supporters (friend, mentor, government agency and/or private agency).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Possessing good business skills is important for all entrepreneurs but particularly for female entrepreneurs because they frequently face structural barriers that make it more difficult to obtain resources (Apergis and Pekka-Economou 2010;Lerner et al 1997;Noguera et al 2013;Pathak et al 2013;Ramadani 2015;Welsh et al 2013). Lack of adequate business skills and other entrepreneurial capabilities negatively affects female entrepreneurs to a greater extent (Botha et al 2006;Carter et al 2015;Itani et al 2011).…”
Section: Perceived Management Skillsmentioning
confidence: 99%
“…In their recent research, Hampel-Milagrosa et al (2015) found that critical factors in the upgrading potential of micro and small firms to medium-and large-sized enterprises included not only the overall quality of the business environment, but also specific entrepreneur and enterprise characteristics, including the gender, education, experience, social capital, ambition, and risk readiness of enterprise owners. Bardasi, Blackden, and Guzman (2007), suggest that male and female-owned enterprises face very similar constraints in their business environment, but that some constraints, including crime, corruption, education levels, and access to finance, affect female-owned enterprises more severely (Bardasi et al, 2007;Brindley, 2005;Singh & Belwal, 2008;Sow-Sar, 2010;Welsh et al, 2013). In addition, traditional gender roles and associated discrimination that limit access to factors such as finance and land ownership can present significant additional barriers to entry into entrepreneurship for women (Desjardins & St-Onge, 2009;Mori, 2014;Mugabi, 2014).…”
Section: Characteristics Of An Enabling Environment For Private Secmentioning
confidence: 99%